Pengaruh Outdoor Learning Dan Minat Belajar Terhadap Prestasi Belajar PAI di SMP Negeri 1 Kejayan - Za’imatun Nabilah, M. Ma’ruf (Al-Makrifat: jurnal kajian Islam, 2024)
Teaching in Islamic Religious Education often becomes less varied with a focus on lectures and question and answer sessions as methods that are often used, making learning less interesting and can cause students to get bored. One important aspect of the teacher's function as an encourage is having a good understanding of the learning model. Apart from that, so that learning can take place according to competency standards, teachers must have various skills that students need, including mastery pertaining to the topic and the ability to use the correct methods. At SMP Negeri 1 Kejayan innovated by implementing outdoor learning in Islamic religious education subjects. Teaching outside the classroom is an effort to create a new atmosphere, raise student enthusiasm, and inspire students to activities that can change their behavior towards the surrounding environment.The objective oh this study is to assess the impact of outdoor learning on PAI learning performance, the effect of learning interest on PAI learning echievement and the combined influence of outdoor learning and learning interest on PAI learning achievement.             This research applies a quantitative approach involving 86 students as research samples. Data was collected by distributing a questionnaire consisting of 13 statements about outdoor learning, 17 statements regarding interest in learning and 10 statements regarding learning achievement in studying Islamic religious education (PAI). The analysis in this research, the method applied includes descriptive analysis and inferential analysis involving simple linear regression and multiple linear regression.Based on descriptive analysis, it shows that there is an influence between outdoor learning variables and interest in learning on PAI learning achievement. Inferential statistical analysis using simple linear regression and multiple linear regression tests obtained results of 2.3% for the influence of Outdoor Learning on PAI Learning Achievement and 18.3% for the results of the influence of Learning Interest on PAI Learning Achievement while for the influence of Outdoor Learning and Learning Interest Regarding PAI Learning Achievement, the results were 19.8%.Keywords: Outdoor Learning, Interest in Learning, Learning Achievement PAI